ANALISIS DATA KUALITATIF: MANUAL DATA ANALISIS PROSEDUR - Rofiah, Chusnul; Burhan Bungin (Develop, 2024)
The purpose of this article is to propose and discuss a Qualitative Data Analysis Guide: Manual Data Analysis Procedures that can be carried out independently by each researcher according to the character of the qualitative method used. Due to the realistic problems faced by qualitative researchers including: (1) Excessive reliance on qualitative software packages, (2) Excess words due to the line-by-line approach (3) Coding using a pre-formed framework, (4) Difficulty in maintaining the integrity of each respondent stories (5) The full potential of data is not exploited (6) Data analysis as an individual process. The author offers a guide to qualitative data analysis: Manual Data Analysis Procedures (MDAP) as a data analysis method that is comprehensive and systematic but not rigid; provide a space that stimulates intuition and creativity as optimally and as fully as possible. This method allows researchers to come out of their isolation and the analysis process is seen as a team activity rather than a purely individual process in order to facilitate the qualitative data analysis process, although it cannot guarantee the quality of the analysis. This method is proposed as a guiding tool rather than as a strict procedure or technique that step by step must be implemented correctly, the skills of the researcher and the general quality of the research team remain the most important components of a successful analysis process. It is very important to consider the data analysis process as a team activity, as long as the research process is not exaggerated, let alone based on conflicts of interest, funding, then whatever research results cannot be applied.